Analysis of Financial Statement Fraud Using the Fraud Triangle Approach (Study on Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange for the Period 2017-2023) - Kurnia, Pedi; Yuniarti, Rita (Dinasti Publisher, 2024)
This study aims to analyze the application of the Fraud Diamond Theory in detecting fraudulent financial statements in manufacturing companies in Indonesia. The Fraud Diamond Theory, which consists of four key elements—pressure, opportunity, rationalization, and capability—provides a comprehensive framework for understanding the factors that drive individuals to commit financial fraud. Using a sample of financial data from selected manufacturing firms, this research examines how these four elements contribute to fraudulent behavior and evaluates their effectiveness in identifying financial statement irregularities. The study utilizes quantitative methods, employing financial ratio analysis, statistical tests, and data on corporate governance to assess the likelihood of fraud within these companies. The results indicate that the elements of pressure and opportunity play a significant role in facilitating fraudulent activities, while rationalization and capability also contribute but are more difficult to quantify. The findings suggest that incorporating Fraud Diamond indicators into corporate governance and internal audit systems can enhance the early detection of financial fraud in manufacturing firms in Indonesia. This research contributes to the growing body of literature on fraud detection, offering insights for regulators, auditors, and corporate stakeholders to strengthen financial oversight and prevent financial misstatements.